User awareness of knowledge management practices of public university libraries in Bangladesh: A study - Mostofa, Sk Mamun; Othman, Roslina (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Users of university libraries frequently have high expectations for the support services offered by the library. The goals of KM are to enhance library services, generate more with fewer resources, prevent duplication of effort, and take advantage of already existing knowledge. Purpose: The main aim of this research is to recognize the user awareness of Knowledge Management (KM) Practices of public university libraries in Bangladesh. Method: The present research used quantitative methods. A total of 1,060 printed questionnaires were distributed among undergraduate (UG) and postgraduate (PG) students of five public university libraries in Bangladesh using a simple random sampling technique. Out of 1,060 questionnaires, 811 usable questionnaires were returned, giving a response of 76.5%. Findings: The study found that users' familiarity with KM is moderately low. They learned about KM through courses provided by their respective departments and independent study through research literature. It was also found that lack of awareness, problems with organizational culture, improper technology deployment, and inadequate support from management are the challenges related to KM practice in public university libraries in Bangladesh. Conclusion: Finally, the research presented managerial and practical implications with further research directions.